KAJIAN PSIKOLOGI INDIVIDUAL DALAM NOVEL WHEN YOU"™RE LOST IN BLUE NOTES KARYA TENUNKATA - Fidela, Raisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Psychological conflicts in the form of feelings of inferiority and compensation efforts experienced by Keisya become a central aspect in shaping the character and storyline in the novel When You're Lost in Blue Notes. This study aims to analyze the forms of feelings of inferiority and compensation experienced by the character Keisya in the novel When You're Lost in Blue Notes by Tenunkata with the study of individual psychology. This research uses hermeneutic reading method with qualitative form. The data source is the text of the novel When You're Lost in Blue Notes by Tenunkata. Data collection techniques, namely direct techniques in the form of documentary studies. The results showed that the forms of inferiority experienced by Keisya's character include timidity, insecurity, increased need for encouragement, and small fantasies. The forms of compensation that appear in Keisya's character include lifestyle, creative self, false goals, and social interests. This research is expected to contribute to the development of literary psychology studies, especially in analyzing the character of novel characters.